2008
DOI: 10.1177/0011128707306689
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Urban Neighborhood Disorder on Evaluations of the Police and Courts

Abstract: Are people dissatisfied with the courts as well as the police when they perceive high levels of disorder in their neighborhoods? Consistent with previous research, this study, using a representative sample of Canadian adults, demonstrates that people are significantly more negative about the police when they perceive high levels of disorder. They are not, however, more negative toward the courts when confronted with these social problems. It is possible that they have heard the police rhetoric—namely, that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 19 publications
(19 reference statements)
9
53
0
Order By: Relevance
“…This expressive perspective already finds support in work from the US (Tyler & Boeckmann, 1997;cf Cao et al, 1996;Reisig & Parks, 2000;Sprott & Doob, 2008) and the UK (Jackson, 2004, Jackson & Sunshine, 2007Jackson & Bradford, 2008). These studies suggest that when the right-wing press highlights ASB, 'youths hanging around,' and public drunkenness, it touches a public nerve which links anxieties about the pace and direction of social change to more local worries about neighbourhood disorder and cohesion (as distinct from anxieties about crime).…”
Section: Figure 2 About Herementioning
confidence: 90%
“…This expressive perspective already finds support in work from the US (Tyler & Boeckmann, 1997;cf Cao et al, 1996;Reisig & Parks, 2000;Sprott & Doob, 2008) and the UK (Jackson, 2004, Jackson & Sunshine, 2007Jackson & Bradford, 2008). These studies suggest that when the right-wing press highlights ASB, 'youths hanging around,' and public drunkenness, it touches a public nerve which links anxieties about the pace and direction of social change to more local worries about neighbourhood disorder and cohesion (as distinct from anxieties about crime).…”
Section: Figure 2 About Herementioning
confidence: 90%
“…For example, using time series regression to analyze 84 months of the BCS data, Sindall and co-researchers (2012) showed that victimization rates were significantly connected to monthly levels of public confidence in the police, whereas public perceptions of crime, disorder, and social cohesion were not predictive. Sprott and Doob's (2009) investigation of the Canadian General Social Survey data revealed that worries about crime and victimization (along with perceptions of neighborhood disorder) lowered public confidence in the police.…”
Section: Distinguishing Expressive Concerns and Instrumental Concernsmentioning
confidence: 99%
“…Individual factors, such as contact with the police (Bartsch & Cheurprakobkit, 2004;Payne & Gainey, 2007;Wells, 2007) and victimization (Brown & Benedict, 2002;Hurst & Frank, 2000;Priest & Carter, 1999), have also been shown to influence perceptions of law enforcement. Finally, neighborhood contextual factors like neighborhood disorder (Ren et al, 2005;Sprott & Doob, 2009), residential mobility (Wu, Sun, & Triplett, 2009), and fear of crime (Brown & Benedict, 2002;Hennigan, Maxson, Sloane, & Ranney, 2002;Wu et al, 2009) also play a role in the formation of attitudes toward the police.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A growing body of literature suggests that citizens' perceptions of their neighborhood have a powerful effect on their views of the police (Brindenball & Jesilow, 2008;Gau & Brunson, 2010;Schafer et al, 2003;Sprott & Doob, 2009). Those who live in areas with high levels of neighborhood "incivilities" are more likely to hold negative opinions of the police (Ren et al, 2005;Sprott & Doob, 2009).…”
Section: Neighborhood Deteriorationmentioning
confidence: 99%
See 1 more Smart Citation